Differences in The Proportion of Factors Related to Occupational Stress on Inspired Nurses During The Covid-19 Draw at Islamic Hospital in Jakarta Pondok Kopi in 2021 - Astri Ulistrianingsih; Munaya Fauziah; Triana Srisantyorini (Muhammadiyah International Public Health and Medicine Proceeding, 2021)
The American National Association for Occupational Health (ANAOH) places the incidence of work stress in nurses at the top of the forty-first on job stress. Work stress experienced by nurses is very detrimental to themselves and the hospital because it can make nurses suffer from fatigue, be rude, anxious, increase blood pressure, decrease self-confidence, increase feelings of dissatisfaction, and can reduce work productivity for nurses. This study was conducted to determine the difference in proportion factors associated with work stress on inpatient nurses during the Covid-19 pandemic at the Pondok Kopi Jakarta Islamic Hospital. Cross-sectional study design with primary data distributed through a questionnaire. The sample is 73 people the sampling is done by incidental sampling. Data analysis used chi-square test (α = 0.05). In this study in the proportion of stress, namely the age of 40 years as many as 28 people (70.0%), female sex as many as 44 (68.8%), married marital status as many as 34 (66.7%), and working years > 6 years as many as 31 (66.0%), heavy workload as much as 50 (70.4%), shift work in the morning shift as much as 37 (63.8%), poor interpersonal relations as much as 44 (86.3%) and who have a UMR salary of 40 (67.8%). The risk factors studied were not related to the incidence of stress in inpatient nurses during the Covid-19 pandemic at the Pondok Kopi Jakarta Islamic Hospital in 2021. It is expected to be input in taking action in anticipating work stress among nurses so that it can improve the performance of nurses in applying quality nursing care.